The clinical-biomechanical assessment of orthosis in patients with bilateral osteoarthrosis of the knee joints - Kovalko, Mykola; Andrukhova, Raisa; Shevchenko, Stanislav; Roman, Lyubov; Vasilenko, Irina (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The application of modern hardware-software complexes for studying statics and walking of patients with bilateral arthrosis of the knee joint, who were supplied with lightweight orthoses out of modern materials, made it possible to objectively assess the efficacy of orthotics.